Reasons for Allowing Muslim Women (Married) to Work Outside the Home - Maftuhah, Aan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Married Muslim women have different characteristics, especially with non-Muslim women. Muslim women who are married, no longer have freedom over themselves according to the Shari'a, especially in matters of earning a living. Because Islam has regulated, that all responsibility for the affairs of the world and the hereafter in the household is on the shoulders of the husband. However, as the situation develops, not all households have complete power in their husbands, so it is not uncommon for some Muslim wives to take the initiative to help ease the burden on their husbands. This situation has also been addressed in Islam, where Muslim wives are allowed to work outside the home with several things, including getting their husband's permission, not mixing with men who are not married, and so on. This research was conducted to obtain actual information about the permission of Muslim women (married) to work outside the home. To answer the research objectives, a qualitative method is used, which is a scientific method that reveals a phenomenon naturally. The research was conducted in the Kranggan area, Central Java, and the research informants were married career women. Research data were collected by means of direct interviews and discussions. The results showed that career Muslim women in the Kranggan area had obtained permission from their husbands to be able to work. As for the reason for working, in general it is to help ease the burden on the husband. There is even a perception that the household is the obligation of husband and wife, so that the wife has the same obligation to help her husband. However, Muslim wives still pay attention to the rules of Religion, about what is allowed and not allowed at work.